If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 6 = -2x + 36 Reorder the terms: 6 + 8x = -2x + 36 Reorder the terms: 6 + 8x = 36 + -2x Solving 6 + 8x = 36 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 6 + 8x + 2x = 36 + -2x + 2x Combine like terms: 8x + 2x = 10x 6 + 10x = 36 + -2x + 2x Combine like terms: -2x + 2x = 0 6 + 10x = 36 + 0 6 + 10x = 36 Add '-6' to each side of the equation. 6 + -6 + 10x = 36 + -6 Combine like terms: 6 + -6 = 0 0 + 10x = 36 + -6 10x = 36 + -6 Combine like terms: 36 + -6 = 30 10x = 30 Divide each side by '10'. x = 3 Simplifying x = 3
| 3c^2-8c=0 | | 2(3x+1)=2(10x-5) | | 5[2x-3]=-15 | | 8+7n-7n=12+4n | | 9(x-3)=4(x-8) | | k(x+4)=2b^2+9b+4 | | 7x-12=-54 | | 20=17x-21x | | 3(3x+2)-4(3x-3)=0 | | 8(6a-1)-6=274 | | (x+27)(x+27)=50 | | 4(p-5)+6p=4 | | 5(x+3)=3y+2 | | 2-8n=-5(n+2) | | (x+27)(x+27)=0 | | 122-5x=22+x | | -3=7x+3 | | -9x-y+1+5y+5x-10+1= | | 15=-2+-1 | | 122-5x=n+22 | | x+4+9=4x+1 | | 7x-8=12x+7 | | 2y+10=3y-18 | | 13m+6n-3m+8n= | | -10-5v-7v=6-8v | | x+4+3=4x+1 | | x^2+54x+679=0 | | 60=-4(-9+x) | | -200=4(6n-2) | | (8.5x)(2.25x)=3000 | | 8x+16=360 | | 25+6x=9x |